Caffeine Mitigates Lung Inflammation Induced by Ischemia-Reperfusion of Lower Limbs in Rats - Wei-Chi Chou; Ming-Chang Kao; Chung-Tai Yue; Pei-Shan Tsai; Chun-Jen Huang (Hindawi Limited, 2015)
Reperfusion of ischemic limbs can induce inflammation and subsequently cause acute lung injury. Caffeine, a widely used psychostimulant, possesses potent anti-inflammatory capacity. We elucidated whether caffeine can mitigate lung inflammation caused by ischemia-reperfusion (IR) of the lower limbs. Adult male Sprague-Dawley rats were randomly allocated to receive IR, IR plus caffeine (IR + Caf group), sham-operation (Sham), or sham plus caffeine (n=12 in each group). To induce IR, lower limbs were bilaterally tied by rubber bands high around each thigh for 3 hours followed by reperfusion for 3 hours. Caffeine (50 mg/kg, intraperitoneal injection) was administered immediately after reperfusion. Our histological assay data revealed characteristics of severe lung inflammation in the IR group and mild to moderate characteristic of lung inflammation in the IR + Caf group. Total cells number and protein concentration in bronchoalveolar lavage fluid of the IR group were significantly higher than those of the IR + Caf group (P<0.001 and P=0.008, resp.). Similarly, pulmonary concentrations of inflammatory mediators (tumor necrosis factor-α, interleukin-1β, and macrophage inflammatory protein-2) and pulmonary myeloperoxidase activity of the IR group were significantly higher than those of the IR + Caf group (all P<0.05). These data clearly demonstrate that caffeine could mitigate lung inflammation induced by ischemia-reperfusion of the lower limbs.